Stabilization and Solidification of Hazardous, Radioactive, and Mixed Wastes: 2nd Volume 1992
DOI: 10.1520/stp19538s
|View full text |Cite
|
Sign up to set email alerts
|

Solidification/Stabilization: Is It Always Appropriate?

Abstract: The findings of recent research and evaluation efforts are assessed to determine whether solidification/stabilization (S/S) has been properly and appropriately applied for different types of hazardous wastes. Results from these studies are mixed and, as a result, the need for proper test procedures and for treatability studies is emphasized. Technical guidance is given for assessing the appropriateness of using S/S for any specific wastes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In addition, Wiles and Barth (1992) of the U.S. Environmental Protection Agency stated: However, results of several studies, as well as data from remediation of several Superfund sites, have raised concerns about whether S/S is a valid technology for treating organic-bearing wastes.…”
Section: Statedmentioning
confidence: 99%
“…In addition, Wiles and Barth (1992) of the U.S. Environmental Protection Agency stated: However, results of several studies, as well as data from remediation of several Superfund sites, have raised concerns about whether S/S is a valid technology for treating organic-bearing wastes.…”
Section: Statedmentioning
confidence: 99%
“…As solubility increases, the metal ion mobility increases. As the pH of the pore fluid in the cement paste is greater than 12, pH control is an important factor in lead retention in the solidified matrix (Wiles and Barth, 1992). Lead retards the set of Portland cement through the formation of insoluble compounds around the silicate phases, hence preventing access of water (Thomas et al, 1981;Ortego et al, 1989;Brown and Bishop, 1990).…”
Section: Leadmentioning
confidence: 99%
“…Previous studies have indicated that chromium must be reduced from chromium(vi) to chromium(iii) prior to any stabilisation in order to form the insoluble chromium(iii) (Wiles and Barth, 1992). Chromium(iii) is most insoluble between pH 5 and 13.…”
Section: Chromiummentioning
confidence: 99%
“…While use of the BDAT is not absolutely required, the treatment that is used must meet the treatment levels specified by the BDAT. There is currently some debate as to whether the applicable regulatory limits for waste forms containing organics are the total concentration limits or the TCLP limits, and whether the TCLP test is a valid test for measuring the leaching of organics (Brown 1992, Spence and Osborne 1991, Wiles and Barth 1992.…”
Section: Regulatory Considerationsmentioning
confidence: 99%
“…The decision of whether to use S/S for a waste containing organics depends on the concentration and characteristics of the organics in the waste and on the characteristics of other components of the waste. Wiles and Barth (1992) developed a decision tree for determining whether to use S/S for organics. They elaborated approaches for determining maximum amounts of organics acceptable for treatment by S/S and for determining acceptability of S/S for a particular waste.…”
Section: Introductionmentioning
confidence: 99%